Mucolipidosis Type IV Protein TRPML1‐Dependent Lysosome Formation. (25th January 2015) - Miller, Austin; Schafer, Jessica; Upchurch, Cameron; Spooner, Ellen; Huynh, Julie; Hernandez, Sebastian; McLaughlin, Brooke; Oden, Liam; Fares, Hanna
Abstract Lysosomes are dynamic organelles that undergo cycles of fusion and fission with themselves and with other organelles. Following fusion with late endosomes to form hybrid organelles, lysosomes are reformed as discrete organelles. This lysosome reformation or formation is a poorly understood process that has not been systematically analyzed and that lacks known regulators. In this study, we quantitatively define the multiple steps of lysosome formation and identify the first regulator of this process. <inline-graphic xlink:href="ark:/27927/pgj4db2nr" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />